Approach for torque ripple reduction for brushless DC motor based on three‐level neutral‐point‐clamped inverter with DC–DC converter. Issue 1 (1st January 2015) - Viswanathan, V.; Jeevananthan, S.
Abstract : This study proposes a novel topology for reducing commutation torque ripple in a brushless DC motor (BLDCM) drive system using a three‐level neutral‐point‐clamped (NPC) inverter combined with single‐ended primary‐inductor converter (SEPIC) converters. In the BLDCM, current ripples arise because of the influence of stator winding inductance, which generates torque ripples. The torque ripple that is generated in the commutation period prevents the use of BLDCM in high‐precision servo drive systems. In this study, two‐stage converters are proposed to reduce the torque ripple. The first stage consists of two SEPIC converters to obtain the desired commutation voltage according to motor speed. A dc‐link voltage selection circuit is combined with the SEPIC converters to apply the optimised voltage during the commutation interval. To reduce the torque ripple further, a three‐level NPC inverter is used to apply a half dc‐link voltage across the motor winding and this effectively reduces the torque ripple. Experimental results show that the proposed topology is able to reduce commutation torque ripple significantly under both low‐speed and high‐speed operation.